Policy congruence in Europe: testing three causal level models at the individual, party and party system levels - Belchior, A. (2016)
Over the last decades, a number of empirical studies have approached representation essentially on the basis of descriptive analyses of political or ideological MP-voter congruence. Only few studies attempted to explain why parties are more or less correspondent to their electorates and none has adopted a comprehensive theoretical approach to that explanation. Trying to respond to this gap, the article begins by assessing the levels of policy preferences among MEPs and their voters using a set of eight policy issues (characterizing the left-right and the libertarian-authoritarian dimensions), and then explores what may explain policy congruence by testing models working at the individual, party and party system levels. Three regression models are run corresponding to each of these levels. Each model regards the eight policy issues under study. The study looks at the political parties of the 27 countries of the European Union (EU) which ran in the 2009 European Parliament (EP) elections. The findings reveal that party congruence is generally moderate (no significant differences seem to emerge between left-right and libertarian-authoritarian issues) and that the individual model (namely voters’ education and intra-party polarization) and party-level model (MEPs’ and voters’ left-right and libertarian-authoritarian attitudes within parties) are those which best explain party policy congruence.